The influence of fluid management on outcomes in preeclampsia: a systematic review and meta-analysis. (May 2018) - Pretorius, T.; van Rensburg, G.; Dyer, R.A.; Biccard, B.M.
Highlights: Data on the ideal fluid management strategy in preeclamptic women is limited. Six randomised controlled trials of fluid management in preeclampsia are reported. It is unclear if colloid volume expansion is harmful. Fluid administration should be individualised. Guidance from non- or minimally-invasive haemodynamic measurements is preferred. Abstract: Background: The optimal fluid management strategy to ensure best outcomes in preeclamptic patients remains a controversial issue, with little evidence to support any one approach. Objective: The aim of this systematic review was to investigate the effect of various fluid management strategies on clinical outcomes, haemodynamic indices and biochemical markers in preeclamptic women and their babies. Primary outcome measures were the occurrence of pulmonary oedema and/or the development of renal impairment. Methods: A systematic review of randomised fluid management strategies was conducted. Five electronic databases were searched using the expanded search terms: 'intravenous fluid', 'plasma substitutes', 'intravenous fluid management', 'intravenous fluid therapy', plasma volume expansion', 'fluid restriction', 'oncotic therapy', 'crystalloids', 'colloids', 'preeclampsia', 'toxemia of pregnancy', 'pregnancy-induced hypertension', 'eclampsia' and 'gestational proteinuric hypertension'. Results: Six randomised controlled trials (RCTs), from nine publications, were included in the final analysis. There were no differences between groups with respect to the incidence of pulmonary oedema, perinatal mortality, preterm delivery and caesarean section. Colloid volume expansion was associated with a significantly lower systolic and diastolic blood pressure, but had no effect on heart rate or cardiac index. Data on systemic vascular resistance (SVR), serum atrial natriuretic peptide (ANP) and urine volume could not be aggregated. Conclusion: Data on the ideal fluid strategy in women with preeclampsia is limited, and insufficient to make any strong recommendations. Further randomised controlled studies are needed to provide more evidence for which fluid management strategies are best suited to this heterogeneous patient group.